Effect of Steam Treatment on the Characteristics of Oil Palm Empty Fruit Bunch and Its Biocomposite - Abdul Muttalib Bin Bujang; Noor Ida Amalina Binti Ahamad Nordin (Universitas Gadjah Mada, 2020)
Oil palm empty fruit bunch (EFB) has a big potential in biocomposite production. The porous surface of EFB is advantageous for physical interlocking with polymer in composite fabrication. The objective of this study is to determine the properties of biocomposite prepared from steam-treated EFB with polypropylene (PP). The EFB was treated using steam at 120 °C for 30 min (Steam-30) and 60 min (Steam-60) in an autoclave. The biocomposite was prepared from EFB and PP at different fiber contents (10 and 30 wt.%). The Steam-30 EFB partially removed silica bodies and other impurities without damaging the surface of the EFB. The thermal stability improved from 276 to 283 °C. The Steam-30/PP biocomposite had the highest tensile strength at 10 and 30 wt.% EFB contents with the increments of 23.9 and 23.8%, respectively, compared to that of the untreated EFB/PP biocomposite. The Steam-30/PP biocomposite containing 30 wt.% of EFB had a low water absorption of 5.6% compared to that of the untreated EFB/PP biocomposite at 7.2%. In conclusion, steam treatment improved the characteristics of EFB and increased the compatibility between the fiber and polymer.